JURIDICAL ANALYSIS OF CHILD AND WIFE NEGLIGENCE IN THE HOUSEHOLD BASED ON SUPREME COURT RULING NO.528K/PID.SUS/2019 - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Siahaan, Efelyn Theresia; Ginting, Haganta Filemon (fakultas hukum universitas PGRI Semarang, 2024)
A household consists of a husband and wife and their dependents. There are many cases when family members commit violence against each other. For example, when a husband or father fails to provide for his family, this is considered household neglect. This research uses a Normative Juridical methodology, which utilizes secondary sources such as books, journals and online sources to compile its findings.Criminals who commit acts of domestic neglect against their wives and children can be prosecuted and sentenced to criminal sentences that are not in accordance with the demands of the Public Prosecutor. This is the crux of the problem. The second way to look at this issue is from a legal perspective, when the judge considers the sentence imposed in the case. Supreme Court judges consider the evidence of defendants and witnesses when handing down sentences. Although the author believes that the punishment imposed by this decision is fair, the author also believes that this term does not discourage violators. As the author argues, it is the judge's responsibility to consider the material and mental well-being of the victim